2018
DOI: 10.1186/s12935-018-0535-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of long non-coding RNA XIST expression in patients with solid tumors: a meta-analysis

Abstract: BackgroundThe aberrant expression of long non-coding RNA (lncRNA) X inactivate-specific transcript (XIST) has been demonstrated to be involved in the tumourigenesis and the development of various cancers. Therefore, we conducted a meta-analysis to assess the prognostic role of lncRNA XIST expression in solid tumors.MethodsThe databases of PubMed, EMBase, Web of Science, Cochrane library (up to Dec 31, 2017) were searched for the related studies and identified 15 eligible studies containing 1209 patients to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…XIST, located on the X chromosome, has previously been reported as a poor prognostic marker in solid tumours. 8 We also found high expression of HCP5-204 that has previously been linked to cancer progression via sponging of miR-22, miR-186 and miR-216a. 9 MALAT1-203 and MALAT1-214, products of metastasis associated lung adenocarcinoma transcript 1 (MALAT1), were downregulated in this study (Table 1).…”
Section: Sirsupporting
confidence: 61%
“…XIST, located on the X chromosome, has previously been reported as a poor prognostic marker in solid tumours. 8 We also found high expression of HCP5-204 that has previously been linked to cancer progression via sponging of miR-22, miR-186 and miR-216a. 9 MALAT1-203 and MALAT1-214, products of metastasis associated lung adenocarcinoma transcript 1 (MALAT1), were downregulated in this study (Table 1).…”
Section: Sirsupporting
confidence: 61%
“…also proved that propofol promotes apoptosis in melanoma cells by suppressing the HOTAIR‐mediated mTOR/p70S6K signaling pathway . A recent study reported that the lncRNA XIST was dysregulated in different cancers and associated with poor clinical outcome . Chen et al.…”
Section: Epigenetic Pathwaysmentioning
confidence: 96%
“…It is well known that epigenetic alterations or genetic modulation of epigenetic regulators plays important roles in carcinogenesis . Many studies show that the anticancer effect of propofol is potentially due to regulation of the epigenetic pathway in cancer …”
Section: Epigenetic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs could regulate a variety of cellular processes including proliferation, apoptosis, invasion, and angiogenesis and therefore exert a pivotal effect in aging, degeneration and carcinogenesis [7,8]. Of late, emerging evidence showed that lncRNAs (such as CASC2, ZEB1-AS1, XIST, and HOXA11-AS) were involved in regulation of cancer related genes and signalling pathways [9][10][11][12]. Meanwhile, numerous lncRNAs have been proved to have potential application as diagnostic biomarkers and therapeutic targets in human cancers [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%